Usability evaluation framework for mobile apps - Rahmat, Hazwani (2020)
Mobile phones have evolved from cell phone to smartphone through various and integrated technology. This technological advancement has transformed mobile apps user interface into a complex interface features. However, the importance of usability in mobile apps has been commonly neglected during the mobile apps’ development life cycle due to the perception of cost and skills required for conducting the usability evaluation. As a result, mobile apps in the marketplace suffers low user retention, which is indicated by the high rate of mobile apps uninstallations after minimal usage. Consequently, extensive frameworks have contributed to addressing usability for mobile phones in various aspects. However, the frameworks are only pertinent mostly in terms of ergonomics, physical user interface, and mobility aspects in using mobile apps. In addition, much of the previous framework conceptualisation was built on desktop computing measurements such as desktop and web applications checklist or scarcely addressed mobile apps user interface. The frameworks focus mainly on the interface features for desktop applications. Therefore, the measurement in the frameworks did not reflect a comprehensive mobile apps interface features such as the navigation drawer and spinner. However, mobile apps are built on different interface features and operating mechanism. Thus, conducting usability evaluation for mobile apps using previous usability evaluation frameworks would result in irrelevant results. Moreover, in real practice, usability evaluation is performed by the non-usability specialist. Lack of usability experience could risk misinterpretation of usability measurement, thus leads to unreliable usability evaluation. Therefore, this study aims to develop a usability evaluation framework for mobile apps that addresses these issues. Initially, a set of usability criteria and interface features are developed to characterise the usability dimension for mobile apps. The usability criteria and interface features are constructed based on content analysis of relevant literature concerning mobile usability measurement, particularly checklist and heuristics. Subsequently, the resulting interface features are enhanced to comply with a user interface in mobile apps of Google Inc. android developer guide. Next, a set of design patterns were conceptualised from the usability criteria to form usability features. The usability features, usability criteria, and interface features are incorporated from the viewpoint of different skills of evaluators. A survey was then administered to assess the comprehensiveness of the usability features and usability criteria in characterising usability dimensions for mobile apps. The usability features and usability criteria are then refined based on the survey responses. Consecutively, a feasibility survey was conducted among industrial software engineering practitioners in Malaysia to evaluate the feasibility of implementing the usability features and usability criteria for usability evaluation of mobile apps in real practice. Finally, the usefulness of the framework measurement for evaluating the usability of mobile apps in view of the non-usability specialist is empirically assessed through an expert review. The experiment is replicated in comparison with a framework from another study. The findings showed that the formulated framework significantly outperformed the framework from another study. Altogether, the two surveys and expert review suggested that the formulated framework is comprehensive, widely acceptable, and more useful compared to another framework. However, the framework focuses on mobile apps for the smartphone. Therefore, these results are not applied to other mobile devices such as feature phones, handhelds, and tablets.